2013
DOI: 10.1080/08964289.2012.720312
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Self-efficacy and Self-help Methods in Women with and without Polycystic Ovary Syndrome

Abstract: Polycystic Ovary Syndrome (PCOS) is a common endocrine disorder in women strongly associated with obesity and psychological dysfunction. It is crucial to assess the contributions of psychological parameters to obesity and weight management. This survey based cross-sectional study assessed self-efficacy, health attitudes and beliefs, response to illness and adult health history in women with (n = 74) and without PCOS (n = 90). There were no significant differences in self-efficacy, health attitudes and beliefs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 47 publications
0
18
1
3
Order By: Relevance
“…Amini et al reported all clinical symptoms of PCOS, including oligomenorrhea, amenorrhea, hirsutism, obesity, decreased fertility, and acne, to contribute to the poorer quality of life of women with this syndrome [29]. Similar to the findings of Deeks et al [13] and in contrast to the results reported by Kozicaa et al [30], we found no significant difference in self-efficacy between women with PCOS and healthy women. Wingo et al concluded that self-efficacy could not affect behavior modification in order to lose weight [31].…”
Section: Discussioncontrasting
confidence: 57%
“…Amini et al reported all clinical symptoms of PCOS, including oligomenorrhea, amenorrhea, hirsutism, obesity, decreased fertility, and acne, to contribute to the poorer quality of life of women with this syndrome [29]. Similar to the findings of Deeks et al [13] and in contrast to the results reported by Kozicaa et al [30], we found no significant difference in self-efficacy between women with PCOS and healthy women. Wingo et al concluded that self-efficacy could not affect behavior modification in order to lose weight [31].…”
Section: Discussioncontrasting
confidence: 57%
“…18 However, only 10% of dietitians reported having a departmental policy regarding PCOS, 18 which may be an opportunity for health services to improve consistent recommendation of lifestyle management. Effective recommendation of lifestyle management is likely to require not only knowledge of the evidence but also skills for supporting women to increase selfefficacy, [34][35][36] and pathways for drawing on the expertise of allied health practitioners. 37…”
Section: Healthcare Providers' Management Strategiesmentioning
confidence: 99%
“…Moreover, Niedermann et al concluded that identifying benefits and barriers to joint protection for arthritis (self-management technique for reducing pain) through qualitative approaches can have a positive impact on communication when individuals are burdened by diabetes (2010). Based on the previous studies mentioned, there is strong support for identifying motivators and barriers to program participation in order to improve public health programming (Lambert et al, 2005;Kozica, 2013Chan et al, 2009Biedenweg et al, 2014. Moreover, an analysis of focus groups with dietary group counseling participants indicated more concrete content for their counseling discussions such as work-related factors, social support, and time management skills (Korkiakangas et al, 2011). Similarly, patients who attended clinical consultations through a diabetes center reported social support as a key factor in managing their diabetes (Black, Maitland, Hilbers & Orinuela, 2017).…”
Section: Diabetes Programsmentioning
confidence: 98%
“…Additionally, qualitative research has also been used to further examine factors related to behavior change for community-based programming. Factors can be related to, but are not limited to, the benefits and barriers and the participants' social support (Lambert et al, 2005;Kozica, 2013Chan, Lok, Sea, & Woo, 2009Biedenweg et al, 2014). These factors are important when reviewing clinical outcomes and evaluating lifestyle programs.…”
Section: Qualitative Studies 4121 Lifestyle Programmingmentioning
confidence: 99%
See 1 more Smart Citation